On-Conditionalism: On the verge of a new metaethical theory - Rønnow-Rasmussen, Toni (Les ateliers de l'éthique / The Ethics Forum, 2016)
This paper explores a novel metaethical theory according to which value judgments express conditional beliefs held by those who make them. Each value judgment expresses the belief that something is the case on condition that something else is the case. The paper aims to reach a better understanding of this view and to highlight some of the challenges that lie ahead. The most pressing of these revolves around the correct understanding of the nature of the relevant cognitive attitudes. It is suggested that the distinction between “dormant attitudes” and “occurrent attitudes” helps us to understand these conditional beliefs.